Hypervalent iodine(iii) induced oxidative olefination of benzylamines using Wittig reagents - Ramavath, Vijayalakshmi; Rupanawar, Bapurao D.; More, Satish G.; Bansode, Ajay H.; Suryavanshi, Gurunath (New Journal of Chemistry, 2021)
We have developed hypervalent iodine(iii) induced oxidative olefination of primary and secondary benzylamines using 2C-Wittig reagents, which provides easy access to alpha,beta-unsaturated esters. Mild reaction conditions, good to excellent yields with high (E) selectivity, and a broad substrate scope are the key features of this reaction. We have successfully carried out the gram-scale synthesis of alpha,beta-unsaturated esters.

Hypervalent-iodine-mediated oxidation followed by the acetoxylation/tosylation of alpha-substituted benzylamines to obtain alpha-acyloxy/tosyloxy ketones - Rupanawar, Bapurao D.; Mane, Kishor D.; Suryavanshi, Gurunath (New Journal of Chemistry, 2022)
An efficient and metal-free method has been developed for the sequential oxidation of alpha-alkylbenzylamines followed by acetoxylation or tosylation for the synthesis of alpha-acyloxy/tosyloxy ketones using hypervalent iodine(iii). The employment of a simple starting material, broad substrate scope and operational simplicity are the key features of this protocol.

Hypervalent-iodine-mediated base-free oxidative olefination of benzylic amines to access α,β-unsaturated ketones - Rupanawar, Bapurao D.; Bansode, Ajay H.; Suryavanshi, Gurunath (Synlett, 2025)
We report a one-pot base-free protocol for the oxidative olefination of benzylic amines promoted by a hypervalent iodine reagent for the synthesis of alpha,beta-unsaturated ketones. Mechanistically, (diacetoxyiodo)benzene oxidizes the benzylic amine to the corresponding imine, which, on reaction with a phenacyl(triphenyl)phosphonium bromide salt and an in situ generated acetoxy anion leads to an alpha,beta-unsaturated ketone. A wide range of alpha,beta-unsaturated ketones were easily accessed through direct oxidative olefination of substituted benzylic amines in good to excellent yields and with high E -selectivity.
Keywords: benzylic amines; enones; hypervalent iodine; olefination; Oxidation